Bilingual modified flipped learning in international nursing education: A discursive approach - Floro Cubelo (Elsevier, 2023)
Finland is experiencing a nurse shortage, leading to the recruitment of internationally educated nurses (IENs). The Finnish education system aims to attract more international students, including those in healthcare. International nursing students (INS) face challenges due to language barriers and cultural differences. This paper introduced the bilingual modified flipped learning (BMFL) approach to address these issues. The BMFL, grounded in constructivist learning theory, incorporated flipped learning and learning stations to facilitate INS integration. It emphasized autonomy and collaboration, with students engaging in pre-class content and in-class interactive activities. The strategy enhanced language skills, clinical decision-making, and communication. Policy and practice recommendations were proposed to support the integration of BMFL, targeting the alleviation of nurse shortages and facilitating the harmonious integration of INS into the Finnish healthcare workforce.